HKA angle exceeding 5 degrees is strongly associated with lateral patellar translation beyond 2 mm: surgical recommendations for avoiding adverse effects on the patellofemoral joint after OWHTO - Zheng Jiang; Nan Zhen; Yanjie Mao; Axiang He; Han Guo; Weiming Lin; Diwen Tang; Yang Qu; Tsung-Yuan Tsai; Wanjun Liu (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Previous studies reported that anterior knee pain (AKP) occurs with an incidence of 32% after opening-wedge high tibial osteotomy (OWHTO). However, the biomechanical effects of this procedure on patellofemoral joints (PFJs) remain unclear. We aimed to quantify the changes in the kinematics and cartilage conditions of the PFJ during stair climbing before and after OWHTO. Methods We recruited 15 patients who underwent unilateral OWHTO. All patients performed continuous stair climbing under the surveillance of a dual fluoroscopic imaging system to determine accurate 6-degree-of-freedom (6-DOF) PFJs and 3D hip-knee-ankle (HKA) angles before and 6 months after OWHTO. The volume penetration centres between the patellar and femoral cartilage models were defined as contact centres. Eleven of these patients underwent quantitative T2 relaxation MRI to determine whether and how PFJ cartilage degeneration progressed. Results After OWHTO, patella valgus (mean − 3.73°, P = 0.02) and internal rotation (mean 3.14°, P = 0.03) increased compared with the preoperative conditions during the stair climbing motion. In addition, the patellae of OWTHO knees were located more laterally after surgery (1.56 ± 2.24 mm, P = 0.02) at knee flexion. Moreover, lateral shifts in the contact patterns of both the medial and lateral patellar facets together with increased T2 values (207.10 ± 21.84 ms, P = 0.04) of the lateral patella cartilage were found after surgery. Finally, the lateral patellar shift increased with decreasing varus 3D-HKA after surgery (R= -0.79, P < 0.001). Therefore, controlling 3D-HKA may be helpful in limiting lateral patellar shift. Conclusion OWHTO changed the patellofemoral kinematics and contact patterns during stair climbing, especially the lateral patellar shift, which may lead to degeneration of the PFJ cartilage. Avoiding overcorrection of the HKA angle beyond 5 degrees of valgus reduces lateral patellar translation, which may help prevent AKP. Additional clinical studies are necessary to validate these biomechanical findings and clarify their impacts on patient outcomes.